VALUE CHAIN ANALYSIS OF SMOKED FISH IN KENJERAN VILLAGE, KENJERAN DISTRICT, SURABAYA CITY - Khoiruddin, Muhamad Alfan; Sahidu, Adriana Monica; Isroni, Wahyu (Journal of Aquaculture Development and Environment, 2024)
Smoked fish products are ready-to-eat because the smoking process is sufficientto cook the fish meat and kill pathogenic bacteria. The fish commonly processed intosmoked fish is milkfish. This research focuses on analyzing the value chain of smokedfish products using a commodity-based and agribusiness area (center) value chainapproach. This aims to comprehensively observe the role of each actor in efforts toincrease added value and produce economically valuable products, especially for theactors within the smoked fish product value chain. This research uses primary andsecondary data collection. The research method used in this study is a descriptivemethod. This study identifies problems in obtaining justification for the currentsituation. This research collects primary data in the form of interview results withMSME actors and questionnaire data, with a total of 10 respondents residing inKenjeran sub-district. This type of research is field research, descriptive qualitative innature, as it seeks to gather existing facts focusing on revealing issues and conditionsas they are. The data collection techniques include interviews and documentation. Theresearch results indicate that smoked fish business actors have already implementedSWOT analysis in running their businesses, but it has not been optimal. This can beseen based on the weighted scores through the Internal Factor Evaluation (IFE) Matrixand the External Factor Evaluation (EFE) Matrix, which show that the positions ofStrengths and Opportunities have higher weighted scores compared to the weightedscores of Threats and Weaknesses